Looking for a Fun Way to Learn English Vocabulary? Discover the Magic of Gamification with Digital Flashcards - Andriani, Miftakul; Sunardi; Drajati, Nur Arifah (Universitas Hamzanwadi, 2024)
Junior high school students learning English as a foreign language (EFL) in countries where English is neither the first nor the second language face significant challenges in acquiring vocabulary due to the infrequent use of English outside the classroom and monotonous teaching techniques. However, in the digital era, innovative educational tools like Digital Flashcard-based gamification offer an interactive and engaging solution. This study aims to understand junior high school EFL students' perceptions of learning English vocabulary through gamification using Digital Flashcards. The research was conducted as Classroom Action Research (CAR) and involved 32 junior high school students in Madiun District, Indonesia, learning English as a foreign language (EFL). Over eight meetings, these students engaged in learning animal-related vocabulary using Digital Flashcard-based gamification. Data were collected through pre-test and post-test and interviews to gather students' perceptions of the learning experience. The results indicate that students' vocabulary mastery significantly improved after using gamification-based Digital Flashcards, with an average increase of 15 points. The pre-test average score was 60, which increased to 75 in the post-test. The gamification elements (story, mechanics, aesthetics, and technology) enhanced students' exposure, attention, and enthusiasm during learning. Vocabulary mastery was effectively facilitated through diverse gamified activities. This study demonstrates that incorporating Digital Flashcards in a gamified format is an effective tool for improving vocabulary learning among EFL students.